1999
DOI: 10.1104/pp.121.1.245
|View full text |Cite
|
Sign up to set email alerts
|

Cytokinins in Tobacco and Wheat Chloroplasts. Occurrence and Changes Due to Light/Dark Treatment

Abstract: Although cytokinins (CKs) affect a number of processes connected with chloroplasts, it has never been rigorously proven that chloroplasts contain CKs. We isolated intact chloroplasts from tobacco (Nicotiana tabacum L. cv SR1) and wheat (Triticum aestivum L. cv Ritmo) leaves and determined their CKs by liquid chromatography/ tandem mass spectroscopy. Chloroplasts from both species contained a whole spectrum of CKs, including free bases (zeatin and isopentenyladenine), ribosides (zeatin riboside, and isopentenyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
50
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(52 citation statements)
references
References 33 publications
2
50
0
Order By: Relevance
“…It has been shown that specific spectra of cytokinin metabolites occur extracellularly as well as in subcellular compartments such as chloroplasts (Faiss et al, 1997;Benková et al, 1999). Sequence analyses of AtCKX proteins predict different subcellular localizations (see below), and the analyses described above of AtCKX overexpressers indicated that the site of enhanced cytokinin degradation might be relevant to the expression of the cytokinin deficiency syndrome.…”
Section: Atckx Proteins Have Different Subcellular Localizationsmentioning
confidence: 99%
“…It has been shown that specific spectra of cytokinin metabolites occur extracellularly as well as in subcellular compartments such as chloroplasts (Faiss et al, 1997;Benková et al, 1999). Sequence analyses of AtCKX proteins predict different subcellular localizations (see below), and the analyses described above of AtCKX overexpressers indicated that the site of enhanced cytokinin degradation might be relevant to the expression of the cytokinin deficiency syndrome.…”
Section: Atckx Proteins Have Different Subcellular Localizationsmentioning
confidence: 99%
“…Exogenously applied cytokinins delay senescence of detached leaves and keep chloroplasts photosynthetically active longer than in control leaves not treated with cytokinins (Romanko et al, 1969). Chloroplasts harbor enzymes for the biosynthesis of cytokinins and contain a set of natural cytokinins, including free bases, ribosides, ribotides, and N-glucosides (Benkova et al, 1999;Kasahara et al, 2004;Polanska et al, 2007). The developmental and/or metabolic state of plastids influences the response of leaves to exogenous cytokinins (Kulaeva et al, 2002).…”
mentioning
confidence: 99%
“…If the suggested electron pathway were true, it would imply that CKX is located on biological membranes and utilizes an intramolecular electron transfer mechanism similar to succinate dehydrogenase (EC 1.3.5.1), a typical Fe-S flavoprotein. In this context, it is interesting that recent observations of tobacco chloroplasts from dark-treated leaves showed that they contained zeatin riboside-O-glucoside and dihydrozeatin riboside-O-glucoside, as well as a relatively high CKX activity [34].…”
mentioning
confidence: 99%